2004
DOI: 10.1523/jneurosci.0757-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Block of AMPA Receptor Desensitization by a Point Mutation outside the Ligand-Binding Domain

Abstract: Desensitization of ionotropic glutamate receptors (GluRs), specifically the AMPA receptor subtype, shapes the postsynaptic response at certain synapses in the brain. All known mechanisms that alter desensitization, either pharmacological or mutational, are associated with the ligand-binding domain. Here we report that substitution of a conserved positively charged arginine (R) with a negatively charged glutamate in the linker between the pore-forming M3 segment and the S2 lobe, a region outside the ligand-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 37 publications
(55 reference statements)
9
101
0
Order By: Relevance
“…Our data lead us to propose the following scheme of regulatory interaction between AMPA receptors and TARPs: until now, chiefly two regions in the AMPA receptor have been linked to the desensitization properties of the receptor, namely the ligandbinding domain (LBD) (Partin et al, 1995;Stern-Bach et al, 1998;Banke et al, 2001;Sun et al, 2002;Horning and Mayer, 2004) and the linker regions between the LBD and the pore region (Yelshansky et al, 2004). Hence, an interaction between the TARP, probably at the first extracellular loop , and one of these two regions of the AMPA receptor seems likely.…”
Section: Possible Role Of Ampa Receptor Domains In Tarp Interactionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our data lead us to propose the following scheme of regulatory interaction between AMPA receptors and TARPs: until now, chiefly two regions in the AMPA receptor have been linked to the desensitization properties of the receptor, namely the ligandbinding domain (LBD) (Partin et al, 1995;Stern-Bach et al, 1998;Banke et al, 2001;Sun et al, 2002;Horning and Mayer, 2004) and the linker regions between the LBD and the pore region (Yelshansky et al, 2004). Hence, an interaction between the TARP, probably at the first extracellular loop , and one of these two regions of the AMPA receptor seems likely.…”
Section: Possible Role Of Ampa Receptor Domains In Tarp Interactionmentioning
confidence: 90%
“…Conversely, an interaction between the TARP and the linker regions connecting the LBD and the pore region cannot be ruled out, especially because it has been shown that point mutations within a linker region influence the desensitization properties of the receptor complexes (Yelshansky et al, 2004). In this case, not only desensitization properties of the receptor complex could be altered but also the gating.…”
Section: Possible Role Of Ampa Receptor Domains In Tarp Interactionmentioning
confidence: 99%
“…Point mutations were generated using PCR-based methods and confirmed by sequence analysis. Human embryonic kidney (HEK) 293 cells were transfected with the cDNAs using X-tremeGene 9 or X-tremeGene HP (Roche Applied Science) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Allosteric potentiators (Jin et al, 2005) bind at the dimer interface, whereas disruptive mutations within the interface accelerate the rate of desensitization (Horning and Mayer, 2004). Kinetic (Bowie and Lange, 2002;Yelshansky et al, 2004) and electron microscopic (Tichelaar et al, 2004) studies also show that the key functional unit of AMPA receptors is a dimer. Most recently, it has been shown that NMDA subunit S1S2 domains form twofold dimers that are stabilized by mutations equivalent to R2 L483Y (Furukawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At several sites within the dimer interface in which mutations to GluR2 had promoted desensitization (Horning and Mayer, 2004), equivalent changes in GluR6 unexpectedly slowed desensitization (Fleck et al, 2003). Furthermore, the dimeric associations identified by kinetic studies in AMPA subunits were either not observed or were weaker in kainate subunits (Bowie and Lange, 2002;Yelshansky et al, 2004). Gating mechanisms also differ, with AMPA subunits gating independently and kainate subunits gating in a concerted manner .…”
Section: Introductionmentioning
confidence: 99%